ADVANTAGES AND DISADVANTAGES OF SURGICAL PROCEDURES IN CHRONIC STOMACH ULCERS - Xalimov Aziz Olim o‘g‘li (World Scientific Research Journal, 2025)
Annotation. This article analyzes research and practical experience on surgical methods for chronic peptic ulcer disease. The article provides information on the effectiveness of surgical interventions for patients with chronic peptic ulcer disease and its possible side effects. Among the achievements are the improvement of the condition of patients, the reduction of symptoms, and the prevention of major complications of the disease. The main shortcomings of the procedure were also discussed in detail, including the risk of infection, the uncertainty of the results of the operation, and the possibility of recurrence of the disease in some patients. This analysis emphasizes the necessity of applying the surgical treatment method according to the correct indications and shows the importance of the final treatment plan in combination with other treatment methods for improving the overall health of patients.